Chemostratigraphy of the Pliensbachian, Puesto Araya Formation (Neuquén Basin, Argentina) - Valencio, Susana Alicia (2005)
In a preliminary attempt to establish an isotope stratigraphy, strontium, carbon and oxygen isotope ratios were determined from marine biogenic carbonates of Pliensbachian age, in the context of scheme of local ammonite Zones correlatable to the European Standard Zonation. Two sections, río Atuel and arroyo Serrucho, of the mainly siliciclastic Puesto Araya Formation, Neuquén Basin, south-western Mendoza, Argentina, were studied. Specimens of the bivalve genera Weyla Bhöm and Gryphaea Lamarck were selected for the isotopic determinations because of their low-Mg calcite original mineralogy and widespread presence. Scanning electron microscopy, X-ray diffraction and X-ray fluorescence spectrometry techniques were used to control the good degree of preservation of most of the biogenic material, as evidenced by pristine fabrics, 100% calcite composition and Sr, Mn and Fe concentrations. Although strontium isotope ratios are slightly scattered, it is possible to compare them with those of the Early Jurassic seawater reference curve. Carbon isotope signals show two relative maxima, correlatable with those recorded for the upper part of the Ibex Zone and the middle part of the Margaritatus Zone in various European sections, indicating the possible global significance of these events. d18O values were found to be unreliable for isotope stratigraphy, as they are largely depleted in comparison to those of coeval unaltered marine carbonates.